KALIMAT IMPERATIF DALAM BAHASA INGGRIS DAN BAHASA SALUAN (SUATU ANALISIS KONTRASTIF) - SOMBA, DEVAKI CHRISTIANI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT Â This research has a title â€œ Kalimat Imperatif dalam Bahasa Inggris dan Bahasa Saluanâ€ and focuses on the types, functions, similarities, and differences of imperative sentences on English and Saluan language. The research questions are: what are the types and functions, and what are the similarities and differences of imperative sentences in English and Saluan language.Â Â The data in English were collected from some English grammar books and data in Saluan language were taken from ten informants who know well about Saluan language using the interview method. After collecting the data, the writer identified and classified the imperative sentences in English and Saluan language. Then the data were analysed using contrastive analysis method, which means that the writer contrasted the data between English and Saluan language to find out the similarities, and differences. There are two types of imperative sentences in English and Saluan language, namely positive and negative imperative sentences. In terms of function, the imperative sentences both in English and Saluan Language have function as command, wish, invitation, instruction and warning. Though the imperative sentences in English and Saluan language have similarities, these languages show differences in terms of the use of words which are related to the socio-cultural aspects. Â Keywords: Imperative sentence, English Saluan language, Contrastive analysis.